Teaching nature of science through the use of media reports on COVID-19. (3rd July 2021) - Demirdöğen, Betül; Aydın-Günbatar, Sevgi
Abstract: Over the past several decades it has become increasingly important to understand nature of science (NOS) for scientific literacy in science education. Science education researchers have suggested using socio-scientific issues to create a context for that purpose. The present fast-moving coronavirus or COVID-19 pandemic as a socio-scientific issue and the abundance of media reports about the pandemic together offer a milieu for putting that suggestion into practice. Therefore, we sought to introduce a guide for how to use media reports on the COVID-19 pandemic to teach NOS. In this paper, we focused on how to use media reports about the COVID-19 pandemic for teaching NOS and relevant science concepts. Moreover, we reviewed the studies investigating how the use of media reports influenced participants' views on NOS. Finally; we described a strategy for teaching NOS through the use of media reports. This strategy involves four steps, namely, (i) finding a suitable media report, (ii) surface analysis of the report, (iii) analysis of NOS aspects and science concepts, and (iv) analysis of the curriculum. In the light of the review and strategy introduced, we offered examples of how to use reports and relate them to NOS aspects in practice.